The Impact of Changes in the Independent Curriculum on Learning in Schools - Abdul Fattah Nasution; Hasita Dwi Putri; Nurtika Syahputri; Laila Parhani Hasibuan; Azaman Andra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The curriculum merdeka has become an increasingly popular approach in recent years, providing greater freedom for schools, teachers, and students to develop and organize their own curriculum. However, these changes also present various challenges and issues in their implementation. This article employs a literature review method to gain a deep understanding of the impact of these changes. The analysis reveals that the curriculum merdeka changes can pose challenges in curriculum development and organization for teachers and schools. There is also a potential gap between schools in implementing the curriculum merdeka. Additionally, the readiness and adequate support for teachers are crucial factors in the success of the curriculum merdeka. To address these challenges, this research emphasizes the importance of adequate training and regular monitoring to improve the quality of learning in schools. By understanding the impact and challenges related to the curriculum merdeka changes, this article aims to provide valuable insights for educational practitioners and policymakers in enhancing the quality of education.